APLIKASI SENSOR KELEMBABAN DAN FLEX SENSOR BERBASIS ARDUINO UNO UNTUK SISTEM PENDETEKSI LONGSOR - Rustan Rustan; Jesi Pebralia; Tika Restianingsih; Frastica Deswardani; Mardian Peslinof; Nurhidayah Nurhidayah; Iful Amri (Prodi Fisika FST UNJA, 2021)
Early detection of landslides is very important to minimize the number of deaths. Technological developments allow humans to predict the signs of landslides more accurately, quickly, and scientifically. In this study, sensors were tested to measure landslide disaster parameters, namely humidity sensors to measure soil moisture and flex sensors to measure soil movement. The sensor is controlled using a microcontroller Arduino Uno. A functionality test was carried out to test the ability of the sensors. The functionality test was carried out using the unit testing method. The unit testing method is carried out by comparing the functional test results of each sensor to the expected response. The moisture sensor functionality test shows that the sensor is able to respond to changes in water content in the soil with changes in voltage. The linear equation resulting from the calibration of the humidity sensor is y = -0.126x + 2.666 with R2 = 0.871. The flex sensor functionality test shows that the sensor is able to detect soil movement in the presence of changes in voltage. The linear equation resulting from the flex sensor calibration is y = -2.861x + 2507 with R2 = 0.964. This shows that the humidity sensor and flex sensor are good enough to be applied in the design of a landslide detection system.